"Our Voter Rolls Are Cleaner Than Yours": Balancing Access and Integrity in Voter List Maintenance. Issue 5 (September 2020) - Merivaki, Thessalia
Accurate voter lists facilitate access to the electoral process, indicate efficient voter list maintenance, and reinforce electoral integrity. Errors in voter records often result from variation in practices that are difficult to avoid given the decentralized structure of election administration in the United States. In many states, localities lack capacity to efficiently complete voter list maintenance, especially when pressured to keep "clean" voter rolls. I argue that local challenges remain when maintaining voters' registration and voting history information, which undermines the quality of voter lists and the integrity of the electoral process. I analyze Mississippi's Statewide Election Management System (SEMS) records and find that voter registration and voting history errors are linked to the county's active and inactive registered voter rates and demographic characteristics. These findings confirm that local variation in voter list maintenance can impact voters depending on their voter registration status and can result in premature voter list removal.